Power point tracker mounted solar powered DC induction cooker - Shams, S M Nasif; Priti, Fahmida Sultana; Saha, Arghya; Haque, M Asif (Bangladesh Journal of Scientific and Industrial Research, 2023)
Induction method of cooking is extensively used for its high effectiveness and safe way of cooking. This paper provides presentation on design and implementation of a solar powered DC induction cooker.The energy from the sun is used as the power source of the cooker. When solar power is not available, the cooker can also be operated by battery. The design of the proposed induction cooker has been developed by modifying conventional AC induction cooker. The main purpose of this cooker is to serve the rural areas where electricity is not always available. Incremental conductance (IC) technique has been used as the procedure of the MPPT which confirms charging of battery by taking in maximum power from the PV panel and the proposed induction cooker will be operated by these batteries. Time taken for cooking different food items has been studied and it is observed that this induction cooker can serve the purpose of cooking for a small family satisfactorily. Bangladesh J. Sci. Ind. Res. 58(3), 135-142, 2023